2022
DOI: 10.2147/ijwh.s376963
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Meconium-Stained Amniotic Fluid at Hadiya Zone Hospitals, Southern Ethiopia; Unmatched Case-Control Study

Abstract: Background Meconium-stained amniotic fluid (MSAF) refers to an amniotic fluid that is green in color or mixed with meconium. MSAF leads to a serious maternal complication that increases the likelihood of operative delivery and poses a hazard to the fetus or the neonate. This in turn enhances the chances of maternal and neonatal mortality and morbidity. So, the identification of determinants helps to breach this vicious cycle. The current study aimed to assess the determinants of MSAF. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…There is an increased risk of meconium staining of liquor in postdate pregnancy, pre-eclampsia, prolonged labour, prelabour rupture of membranes, fetal distress, and intrauterine growth restriction. 22 Our findings are supported by the studies of Bajracharya N and Wood SL who also observed no significant increase in meconium staining of amniotic fluid (p=0.216& p=0.23 respectively). 20,21 Vyas A noted a higher rate of passage of meconium in cases of borderline AFI ( 27% versus 11%, p=0.006).…”
Section: Discussionsupporting
confidence: 88%
“…There is an increased risk of meconium staining of liquor in postdate pregnancy, pre-eclampsia, prolonged labour, prelabour rupture of membranes, fetal distress, and intrauterine growth restriction. 22 Our findings are supported by the studies of Bajracharya N and Wood SL who also observed no significant increase in meconium staining of amniotic fluid (p=0.216& p=0.23 respectively). 20,21 Vyas A noted a higher rate of passage of meconium in cases of borderline AFI ( 27% versus 11%, p=0.006).…”
Section: Discussionsupporting
confidence: 88%
“…According to studies, 20%–33% of neonates born with meconium have neurologic and respiratory depression, suggesting chronic exposure to a hypoxic environment ( 4 , 16 , 21 , 22 , 38 , 39 ). Most of the studies associate the stage of labor with the incidence of meconium-stained amniotic fluid ( 37 , 38 , 40 , 41 ), but some studies associate labor abnormalities ( 25 ) with MAS.…”
Section: Discussionmentioning
confidence: 99%
“…Meconium is the first substance found in the developing foetus's intestines and constitutes the new-born's first bowel movement. Green, brown, or yellow meconium is possible [52].…”
Section: Meconium Staining Liqourmentioning
confidence: 99%